Financial performance of Iranian banks from 2013 to 2019: A panel data approach - Pejman Ebrahimi; Maria Fekete-Farkas; Parisa Bouzari; Róbert Magda (Journal of Risk and Financial Management, 2021)
It is widely believed that the financial system is dependent on the banking industry, and its strength and development are vital for economic prosperity. This paper tried to show the financial performance of Iranian banks listed on the Tehran Stock Exchange (TSE) during 2013-2019, as the research population. The statistical population included 18 banks listed on the TSE from 2013 to 2019, which were sampled using a screening method. The results indicated a significant relationship between explanatory variables of capital ratio and the financial performance of banks in all models. However, a significant negative relationship was found between the inflation rate and the financial performance of banks in all models. Furthermore, it seems that banks with high asset strength are more profitable than the others. Regulators should guarantee that banks remain highly capitalized for a viable banking sector in Iran.
Keywords: 330; bank-specific factor; financial performance; macroeconomic factors; panel data